Influence of food products on oxidation-reduction state in diseases of the respiratory tract - A.E. Abaturov; A.P. Volosovets; T.P. Borysova (Zdorovʹe Rebenka, 2017)
The review of the literature presents current data on the content of antioxidants in food products. Dietary factors regulating the production of nitrogen monoxide are presented. The influence of the antioxidant diet on the probability of development and course of chronic respiratory diseases is shown.